2019
DOI: 10.1037/pap0000177
|View full text |Cite
|
Sign up to set email alerts
|

Therapist–client language matching: Initial promise as a measure of therapist–client relationship quality.

Abstract: While research suggests that the therapeutic alliance is important in predicting outcomes of psychotherapy, relatively little is known about the development of the alliance or the moment-to-moment components of the relationship and how they combine to create an alliance, which may represent a serious limitation in existing methods of measurement. Language style matching (LSM), or the degree to which unconscious aspects of an interactional partner’s language mimic that of the other partner, is a promising, unob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 70 publications
4
20
0
1
Order By: Relevance
“…While some studies have examined neurophysiological measures such as EEG, this is not an area that has been widely explored in the psychotherapeutic context (Stratford et al 2012). In studies that examined physiological coordination over time, no clear pattern across studies was identified except that the strength of the coordination changes both within and across sessions (Di Mascio et al 1955;Stratford et al 2012Stratford et al , 2014 and that coordination levels in early sessions may be related to diagnoses (Paulick et al 2018b), symptom reduction (Borelli et al 2019), and dropout (Paulick et al 2018a). Further, physiological coordination was primarily linked to measures of empathy and emotion (Marci et al 2007;Marci and Orr 2006;Messina et al 2013) with no direct links between physiological coordination and psychotherapy outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies have examined neurophysiological measures such as EEG, this is not an area that has been widely explored in the psychotherapeutic context (Stratford et al 2012). In studies that examined physiological coordination over time, no clear pattern across studies was identified except that the strength of the coordination changes both within and across sessions (Di Mascio et al 1955;Stratford et al 2012Stratford et al , 2014 and that coordination levels in early sessions may be related to diagnoses (Paulick et al 2018b), symptom reduction (Borelli et al 2019), and dropout (Paulick et al 2018a). Further, physiological coordination was primarily linked to measures of empathy and emotion (Marci et al 2007;Marci and Orr 2006;Messina et al 2013) with no direct links between physiological coordination and psychotherapy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, when the therapists' vocal pitch followed the patients' vocal pitch more strongly, an increase in symptoms was observed (Reich et al 2014); however, when comparing a good outcome sessions to a poor outcome session, stronger coordination of speech rate between therapist and patient was associated with the better treatment outcome (Rocco et al 2016). Moreover, another study showed that higher language style matching during early phases of treatment was associated with symptom reduction (Borelli et al 2019). While vocal pitch, speech rate, and language style are different aspects of vocalizations, these results suggest that even within a given modality there can be variability regarding how interpersonal coordination is related to psychotherapy outcomes (i.e., associated with better or worse outcomes).…”
Section: Links To Psychotherapy Outcomesmentioning
confidence: 99%
“…Production of function words is typically independent of the content of the topic of discussion (Gonzales et al, 2010) and is an aspect of language that is difficult, if not impossible, to consciously monitor or influence in the self or others (Chung & Pennebaker, 2007). By evaluating the similarity of function-word use across members of a dyad, the LSM metric enables the examination of an aspect of linguistic behavior, and potentially of relationship quality (Borelli et al, 2019), of which participants are not aware, and that is unrelated to the topic of their speech (Ireland & Pennebaker, 2010).…”
mentioning
confidence: 99%
“…As of yet, only three empirical studies have reported on the application of LSM in the therapeutic relationship (Aafjes‐van Doorn, Porcerelli, & Müller‐Frommeyer, ; Borelli et al, ; Lord, Sheng, Imel, Baer, & Atkins, ). These studies reported that the extent to which the therapist and the client are matched in their language style is associated with therapist empathy and treatment outcome, suggesting that LSM may provide a deeper understanding of a quality of the therapeutic interaction.…”
Section: Language Style Matchingmentioning
confidence: 99%